2013
DOI: 10.3390/ijerph10062515
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional, Randomized Cluster Sample Survey of Household Vulnerability to Extreme Heat among Slum Dwellers in Ahmedabad, India

Abstract: Extreme heat is a significant public health concern in India; extreme heat hazards are projected to increase in frequency and severity with climate change. Few of the factors driving population heat vulnerability are documented, though poverty is a presumed risk factor. To facilitate public health preparedness, an assessment of factors affecting vulnerability among slum dwellers was conducted in summer 2011 in Ahmedabad, Gujarat, India. Indicators of heat exposure, susceptibility to heat illness, and adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 15 publications
5
72
1
Order By: Relevance
“…The humanitarian impact of these heat waves was large, with 40 % of all extreme-weather-related deaths attributed to heat waves in 2016, which is the largest proportion of total deaths of any type of extreme weather event (India Meteorological G. J. van Oldenborgh et al: Extreme heat in India and anthropogenic climate change Department, Climate Research and Services, 2017). Experience in implementing heat wave interventions has shown that these deaths can be greatly reduced by straightforward measures such as keeping parks and homeless shelters open on the hottest days and providing early warning of a forecasted heat wave (Fouillet et al, 2008;Tran et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The humanitarian impact of these heat waves was large, with 40 % of all extreme-weather-related deaths attributed to heat waves in 2016, which is the largest proportion of total deaths of any type of extreme weather event (India Meteorological G. J. van Oldenborgh et al: Extreme heat in India and anthropogenic climate change Department, Climate Research and Services, 2017). Experience in implementing heat wave interventions has shown that these deaths can be greatly reduced by straightforward measures such as keeping parks and homeless shelters open on the hottest days and providing early warning of a forecasted heat wave (Fouillet et al, 2008;Tran et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This happened in Europe up to the mid-1980s (e.g. and there is evidence that this plays a role in India (Krishnan and Ramanathan, 2002;van Donkelaar et al, 2015;Padma Kumari et al, 2007;Wild et al, 2007). The third mechanism is an increase in irrigation (Ambika et al, 2016) that leads to higher moisture availability and hence increased evaporation, leaving less energy to heat the air.…”
Section: Temperature Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time series analysis was also employed to identify the serial correlations and trends over time, seasonal variations over time and the possibility of forecasting future dengue outbreaks. More importantly Trang et al [18], developed an autoregressive integrated moving average (ARIMA) model to predict future dengue outbreaks in a cross sectional randomized cluster sample survey [19] of districts in Sri Lanka using GIS as a tool to identify dengue risk associated with population density, land pattern and climatic factors. GIS was employed to design a dashboard for health authorities to survey high-risk areas for control.…”
Section: Methodsmentioning
confidence: 99%
“…On a micro scale, slums and informal settlements, generally occupied by the poor, face disproportionately greater risks related to climate change 25 and health 26 . They are often unplanned, lacking both the infrastructure and service base of wealthier neighborhoods.…”
Section: Unequal Impactsmentioning
confidence: 99%